Chapter La struttura territoriale della bioregione urbana: pianificare sistemi multipolari autosostenibili e solidali. Il caso della Puglia - barbanente, angela (Territori, 2023)
The concept of urban bioregion provides an interpretive and design perspective to the critical vision of planetary urbanisation, pursuing the recovery of co-evolutionary relations between human settlement and the environment through the reconstruction both of the 'urbanity' of places in plural and multi-centred forms and of the relations between urban and rural life-worlds. The experience of the Apulia Regional Landscape Plan is presented as an attempt of policy and planning innovation aimed at supporting re-inhabiting practices consistent with the principles and forms of the urban bioregion. The Plan promotes projects and actions characterised by a multi-scalar dimension, which assume as key factors for a just and regenerative local development the re-establishment of co-evolutionary relationships between human settlement and the geo-environmental system, the mobilisation of local knowledge, and the shaping of a sense of belonging to places and inhabitants' care practices.